2017
DOI: 10.1074/mcp.ra117.000104
|View full text |Cite
|
Sign up to set email alerts
|

A Varroa destructor protein atlas reveals molecular underpinnings of developmental transitions and sexual differentiation

Abstract: Varroa destructor is the most economically damaging honey bee pest, weakening colonies by simultaneously parasitizing bees and transmitting harmful viruses. Despite these impacts on honey bee health, surprisingly little is known about its fundamental molecular biology. Here, we present a Varroa protein atlas crossing all major developmental stages (egg, protonymph, deutonymph, and adult) for both male and female mites as a web-based interactive tool (http://foster.nce.ubc.ca/varroa/index.html). We used intensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…Lipid transport involving vitellogenin (Vg) is the most significantly enriched biological process in the foundress (reproductive female) and in young mites (McAfee et al 2017), suggesting that honey bee Vg may be altered by Varroa infestation. However, in our study, no alteration of Vg was found in 1-day-old honey bee haemolymph after Varroa infestation.…”
Section: Proteins Of Branched Chain Amino Acid Metabolism and Lipid Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid transport involving vitellogenin (Vg) is the most significantly enriched biological process in the foundress (reproductive female) and in young mites (McAfee et al 2017), suggesting that honey bee Vg may be altered by Varroa infestation. However, in our study, no alteration of Vg was found in 1-day-old honey bee haemolymph after Varroa infestation.…”
Section: Proteins Of Branched Chain Amino Acid Metabolism and Lipid Mmentioning
confidence: 99%
“…Recently, proteomics analysis has been used in studies of Varroa destructor mites (Erban et al 2015;McAfee et al 2017;Iovinella et al 2018). Several groups of proteins were identified in Varroa females, as follows: (i) proteins of virions such as Varroa destructor Macula-like virus, DWV and acute bee paralysis virus (Erban et al 2015); (ii) a variety of honey bee haemolymph proteins, including apolipophorin, hexamerins and various major royal jelly proteins (Erban et al 2015); and (iii) key proteins that may act as semiochemical carriers, such as odorant-binding proteins and Niemann-Pick family, type C2 proteins (Iovinella et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, transcriptomic analysis were performed on Varroa destructor synganglion [ 15 ] and foreleg (olfactory organ) [ 16 ]. A proteomic analysis was also performed on V. destructor , with a focus on the different developmental stages of the mite [ 17 ]. In addition, differential gene expression was investigated in V. jacobsoni with respect to the host on which they reproduce [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We performed all further proteomics sample preparation steps exactly as previously described. 58 Briefly, we used urea digestion buffer to solubilize the protein, then reduced (dithiothreitol), alkylated (iodoacetamide), diluted with four volumes of 50 mM ammonium bicarbonate, digested (Lys-C for 3 h, then trypsin overnight), and desalted peptides using C18 STAGE tips made in-house. We suspended the desalted, dried peptides in Buffer A, then estimated peptide concentration by the absorbance at 280 nanometers (Nanodrop).…”
Section: Proteomics Sample Preparationmentioning
confidence: 99%